Samotność jako mistyczna ciemność. Św. Jan od Krzyża i bł. Matka Teresa z Kalkuty - Grzegorczyk, Anna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
The “dark night” – painful feeling being abandoned by God – was experienced by many masters of spiritual life, by saint John of Cross as well as by blessed Mother Teresa, as is shown in her memoirs. Authoress claims that, paradoxically, this apparently declining experience is just a stage that has to be passed in order to achieve fullness of mystic insight and spiritual growth. Doubts, grief, lack of power and will – all this feelings are not the symptoms of spiritual collapse but a steps on a way into holiness. The God is the one who gives the power to overcome typically human weaknesses andcrises (solitude, isolation, adversities).